Endoscopic carpal tunnel release: a prospective study of functional outcome - Thuraisingham, R.; Ahmad, T.S.; Loh, Y.C. (Malaysian Orthopaedic Association, 2009)
To evaluate the functional outcome of patients who underwent endoscopic carpal tunnel release (ECTR). This was a prospective study in 24 patients with idiopathic carpal tunnel syndrome undergoing ECTR . Patient assessment entailing both subjective and objective tests at intervals of two and six weeks, three, six and nine months and finally at one year postoperatively. Our assessment results showed overall improvement in symptoms. As early as two weeks post-operatively, there was a low incidence of pillar pain and scar tenderness, allowing patients to return to work early. There were no serious complications. ECTR can be effectively performed with a low perioperative and late postoperative rate of complications. This minimally invasive method can be an option of surgical treatment for patients with carpal tunnel syndrome, who intend to return to work soon after surgery.